Implementation of Al-Ghazali's Ushul Fiqh Method on The Issues of Apostasy and Religious Freedom in Indonesian Muslim Society - Ansori, Ikhwan (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2026)
The application of the death penalty for apostates (riddah) risks undermining the image and harmony of Islam within Indonesia's diverse socio-legal environment. In a constitutional state that guarantees freedom of religion, the issue of apostasy must be reexamined through a critical reinterpretation of traditional fiqh principles. This study dialogues classical arguments on riddah with the principle of religious freedom in Indonesia, employing Imam Al-Ghazali's ushul fiqh theory in Al-Mustashfā as the analytical framework. Al-Ghazali was selected precisely because he endorsed the death penalty for apostasy, making a constructive re-reading of his methodology particularly significant. Through critical analysis, this study demonstrates that by applying Al-Ghazali's istishlah (public interest) approach—grounded in the same sources of the Qur'an, Sunnah, and maslahat used by proponents of capital punishment—the death penalty for apostasy is not relevant in the Indonesian context. This study offers an adaptive fiqh paradigm that prioritizes public benefit, constitutional rights protection, and social harmony. Al-Ghazali's historical argument on apostasy, while suited to his era, yields a renewed interpretation through the lens of hifdzu ad-din that favors religious freedom over harsh punishment in pluralistic societies such as Indonesia.